2020
DOI: 10.1002/ange.201909909
|View full text |Cite
|
Sign up to set email alerts
|

Durch definierte Rhodiumkomplexe vermittelte Polymerisationen

Abstract: Dieser Kurzaufsatz präsentiert den aktuellen Stand von (Co)polymerisationen, die von definierten Ethinyl‐, Vinyl‐ und Aryl‐RhI‐Komplexen vermittelt werden. Dabei konzentrieren wir uns auf RhI‐Verbindungen, die sich für die (Co)polymerisation von Phenylacetylenen, Arylisocyaniden sowie Propargylestern und ‐amiden eignen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Clearly, PPh 3 retarded the propagation step by coordinating to rhodium. [10][11][12][13][14][15] From these results,w er ealized that the aryl rhodium(I) species formed from boronic acid 1a did not function as an efficient initiator for the polymerization of 5a. Other boronic acids were also tested, but the results were not improved.…”
Section: Design and Development Of The Catalytic Systemmentioning
confidence: 97%
See 1 more Smart Citation
“…Clearly, PPh 3 retarded the propagation step by coordinating to rhodium. [10][11][12][13][14][15] From these results,w er ealized that the aryl rhodium(I) species formed from boronic acid 1a did not function as an efficient initiator for the polymerization of 5a. Other boronic acids were also tested, but the results were not improved.…”
Section: Design and Development Of The Catalytic Systemmentioning
confidence: 97%
“…[8,9] However,e xamples of the controlled polymerization of substituted acetylenes are still sparse as compared to those of vinyl monomers. [10] In 1994, Noyori and coworkers reported living polymerization of phenylacetylenes using ac ombination of the rhodium(I) complex Rh(CCPh)(nbd)(PPh 3 ) 2 and N,N-dimethylaminopyridine (DMAP). [11] Following that report, they also showed that similar living polymerization was possible with ac onvenient multicomponent catalytic system composed of [Rh-(nbd)OMe] 2 /PPh 3 /DMAP or [Rh(nbd)Cl] 2 /NaOMe/PPh 3 / DMAP (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…A suitable crystal 0.25 mm × 0.17 mm × 0.10 mm was selected and mounted on a suitable support on an XtaLAB Synergy, single source at home/near, HyPix diffractometer. The crystal was kept at a steady T = 120.01 (10) K during data collection. The structure was solved with the ShelXT structure solution program using the Intrinsic Phasing solution method and by using Olex Computational Chemistry.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The transition-metal-mediated (co)­polymerization of arylacetylenes, including 1-substituted and 1,2-disubstituted substrates, in a noncontrolled manner, is well documented. In distinct contrast, there is a notable dearth of literature reports concerning the living (co)­polymerization of arylacetylene monomers and related alkyne substrates such as propargyl esters/amides and arylisocyanides. With regard to arylacetylenes, Kishimoto et al were the first to report the living polymerization of phenylacetylene (PhC 2 H) employing an in situ generated pentacoordinate rhodium-alkynyl species, Rh­(nbd)­(CCPh)­(PPh 3 ) 2 (nbd = 2,5-norbornadiene). This complex was isolated, and the solid-state structure reported with the species adopting a slightly distorted trigonal bipyramidal geometry.…”
Section: Introductionmentioning
confidence: 99%